Preparation method and application of composite 3D negative electrode current collector for lithium metal battery

By introducing reduced graphene oxide artificial interface layer and three-dimensional micro pit array structure on the current collector surface of the lithium metal battery, the volume expansion and safety hazards caused by lithium dendrites during the battery cycle are solved, and the uniform deposition of lithium metal and the excellent circulation performance of lithium copper half-cell are achieved.

CN119650711APending Publication Date: 2025-03-18HARBIN INST OF TECH +1

Patent Information

Application Number
CN202411821444.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing lithium metal negative electrodes are prone to lithium dendrites during battery circulation, resulting in volume expansion and safety hazards. It is difficult to effectively inhibit the appearance of lithium dendrites by traditional structural modification and artificial interface layer addition methods.

Method used

The reduced graphene oxide artificial interface layer is introduced on the current collector surface by chemical coating, and on the basis of it, the three-dimensional micro pit array structure is introduced through laser etching, the current density distribution on the surface of the current collector is adjusted, the uniform deposition of lithium metal is induced and the formation of lithium dendrites is inhibited.

Benefits of technology

The uniform deposition of lithium metal on the macroscopic and microscopic scales has been achieved, which significantly inhibits the formation of lithium dendrites, improves the circulation performance of lithium copper half-cells, and ensures the safety and efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650711A_ABST
    Figure CN119650711A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite 3D negative electrode current collector for a lithium metal battery, and belongs to the field of batteries, and the preparation method comprises the following steps: firstly, introducing a reduced graphene oxide artificial interface layer on the surface of the current collector through a chemical coating means, so that the reduced graphene oxide artificial interface layer and the current collector are tightly combined and are not easy to fall off after being bent due to chemical reaction in the process; and the conductivity and the ductility of the coated current collector are not greatly damaged. Then, on this basis, a three-dimensional micro-pit array structure with a lithium-loving oxide layer is introduced on the surface of the current collector by means of laser etching, so that the specific surface area of the current collector is increased, the surface current density distribution is adjusted, lithium metal is effectively induced to be uniformly deposited on the macro-scale and the micro-scale, and formation of lithium dendrites is inhibited; the lithium copper half battery assembled by the current collector has excellent cycle performance. The preparation process flow is simple, the composite 3D current collector with excellent performance is prepared, the cost is effectively reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and specifically relates to a composite 3D negative electrode current collector for lithium metal batteries and a preparation method and application thereof. Background Art

[0002] As the world pays more attention to environmental issues and energy sustainability, the electric vehicle market and large-scale energy storage systems are growing stronger and stronger. Lithium batteries are currently the most widely used energy storage materials, with advantages such as high energy density and long cycle life, which have strongly promoted the vigorous development of the new energy market. However, the energy density of traditional lithium-ion battery systems based on graphite anodes has approached the theoretical limit and is difficult to be further improved. Replacing the graphite anode with a lithium metal anode can effectively reduce the weight of the battery and increase its energy density. At the same time, the lithium metal anode also has the lowest electrode potential and low internal resistance, which can effectively improve the rate performance of the battery. However, due to the lack of materials that can accommodate lithium ions in the anode, lithium metal selectively nucleates and grows directly on the surface of the current collector, causing huge volume expansion and safety hazards during the battery cycle, which seriously hinders the commercialization of lithium metal anodes. Combined with the reaction process and failure mechanism of lithium metal anodes obtained in the study, in order to promote and realize the commercialization of lithium metal batteries, scientists have made great efforts in two aspects, namely the basic research of lithium dendrites and SEI (Solid electrochemical interface). At present, the modification strategies for lithium metal anodes are mainly to add an artificial interface layer on the surface of the current collector and design the structure of the current collector. Adding an artificial interface layer can effectively protect the lithium metal anode from serious interface side reactions with the electrolyte and promote the formation of a more stable SEI layer. The prepared lithium metal anode can maintain a more stable state during the lithium-copper half-cell cycle. By designing the structure of the current collector and changing the structure and size of the current collector, the current density and ion concentration can be evenly distributed on the entire surface of the current collector, effectively inhibiting the growth of lithium dendrites and better meeting the use requirements and safety specifications.

[0003] At present, researchers hope to modify the copper current collector to make the current density distribution on the current collector surface more uniform and the interface contact with the electrolyte more stable, so as to delay the appearance of lithium dendrites. However, a single structural modification or the addition of an artificial interface layer cannot effectively limit the appearance of lithium dendrites. The general structurally modified three-dimensional current collector can effectively reduce the absolute current density on the current collector surface and regulate the surface current density distribution, but the three-dimensional skeleton without lithium affinity and the uncontrollable structural pathway will cause lithium metal to accumulate on the surface of the three-dimensional current collector, reducing the space utilization rate and eventually causing the disordered growth of lithium dendrites on the surface; adding a lithium-philic artificial interface layer on the current collector surface can effectively induce the uniform deposition of lithium metal on the plane, but the low specific surface area will lead to excessive current density in some areas and cannot limit the volume expansion of lithium metal during the cycle. Adding an artificial interface layer on the basis of the three-dimensional current collector can effectively improve the shortcomings of the above two methods, but most of the current preparation methods are relatively cumbersome. It is very difficult to add a thin and evenly distributed interface layer on the basis of the three-dimensional structure, and the prepared three-dimensional structure skeleton is often very smooth. The general chemical coating method cannot evenly cover the three-dimensional skeleton. The chemical vapor deposition method can evenly deposit an artificial interface layer on the three-dimensional structure skeleton, but this method is undoubtedly inefficient and cumbersome, and is not conducive to large-scale commercial production. The general means of coating the artificial interface layer cannot achieve a good coating effect, and may even cause blocking of the three-dimensional holes, resulting in a decrease in the performance of the current collector.

[0004] CN110212153A, the invention title "A current collector and its preparation method" discloses a method for preparing a current collector, including the following operations: immersing a metal substrate in a graphene oxide solution; cleaning the immersed metal substrate; drying the cleaned metal substrate. The concentration of the graphene oxide solution is 0.1-2 mg / mL; the metal substrate is immersed in the graphene oxide solution for 10-240 min; the metal substrate is aluminum foil or copper foil. The method for preparing a current collector provided by this patent corrodes the surface of a metal substrate (such as aluminum foil or copper foil) to form a convex or concave structure on its surface, and automatically coats a thinner graphene layer on its surface to improve the conductivity of the current collector. This method realizes surface roughening treatment and coating of a graphene layer in one step, with simple steps and easy operation.

[0005] However, the purpose of adding graphene in this patent is to improve the interface performance between the current collector and the positive and negative electrode materials, such as bonding strength, interface resistance, etc. It cannot be used directly as a negative electrode. This patent first corrodes the metal substrate to obtain a current collector with a protrusion and depression structure, and then coats the graphene interface layer. There is a problem of uneven thickness of the graphene interface layer caused by protrusions or depressions, and there is an uneven deposition of lithium metal at the negative electrode interface, which cannot effectively alleviate the problem of the appearance of lithium dendrites. Summary of the invention

[0006] The present invention provides a modified copper current collector that is easy to prepare and has low cost, as well as a preparation method and application thereof. In order to achieve this purpose, the present invention first introduces a reduced graphene oxide artificial interface layer on the surface of the current collector by means of chemical coating. Since the two react chemically during the process, they are tightly combined and are not easy to fall off after bending, and the conductivity and ductility of the coated current collector are not greatly damaged. Subsequently, on this basis, a three-dimensional micro-pit array structure with a lithium-philic oxide layer is introduced on the surface of the current collector by means of laser etching, thereby increasing the specific surface area of ​​the current collector, adjusting the surface current density distribution, effectively inducing the uniform deposition of lithium metal on a macroscopic and microscopic scale, and inhibiting the formation of lithium dendrites. The lithium-copper half-cell assembled by the current collector has excellent cycle performance.

[0007] The preparation method of a composite 3D negative electrode current collector for a lithium metal battery of the present invention is carried out in the following manner:

[0008] 1) Clean the copper foil to remove the surface oxide layer;

[0009] 2) soaking the cleaned copper foil in a graphene oxide suspension, and vacuum drying the copper foil with graphene oxide attached to the surface after soaking;

[0010] 3) The copper foil with graphene oxide attached to the surface after drying is patterned by laser etching to obtain a three-dimensional current collector with graphene coated on the surface.

[0011] Furthermore, the copper foil has a thickness of 20-50 μm.

[0012] Furthermore, the concentration of the graphene oxide suspension is 0.5-1.0 mg / mL.

[0013] Furthermore, the soaking time is 12h-24h, and the soaking temperature is room temperature.

[0014] Furthermore, the vacuum drying temperature is 150-180° C., and the vacuum drying time is 8 h-12 h.

[0015] Furthermore, the laser-etched pattern is a pattern composed of uniformly distributed micro-pit array lattices.

[0016] Furthermore, the laser etching process conditions are as follows: the aperture is set to 50-75 μm, the hole spacing is set to 50-200 μm, the laser etching scanning speed is set to 100-500 Hz, the scanning power is set to 10 W, and the number of scans is set to 5-10 times.

[0017] The present invention discloses an application of a composite 3D negative electrode current collector for a lithium metal battery. The composite 3D negative electrode current collector for a lithium metal battery is used to prepare a lithium-copper half-cell.

[0018] The present invention has the following beneficial effects:

[0019] 1) The present invention uses simple and efficient laser etching and chemical coating methods to construct a high-performance current collector with an artificial interface layer and a three-dimensional structure. Abandoning the traditional technical route of "first building a three-dimensional structure and then adding an artificial interface layer", the present invention first introduces a uniformly distributed artificial interface layer on the surface of the current collector by chemically coating graphene, and then etches the surface of the current collector by low-power laser, introducing a three-dimensional structure without damaging the original artificial interface layer.

[0020] 2) First, an artificial interface layer is introduced on the surface of the current collector by means of chemical coating. The graphene oxide interface layer is evenly distributed on the surface of the copper current collector. At the same time, the graphene oxide will be converted into a reduced graphene oxide interface layer during the contact with the copper current collector, which effectively improves the surface conductivity and current density distribution.

[0021] 3) On the basis of coating the artificial interface layer, a pit array structure is introduced on the surface of the current collector by laser scanning line by line, which effectively adjusts the current density distribution on the surface of the current collector. Due to the small aperture and low laser power, the artificial interface layer around the micro-pits is not damaged. In addition, during the processing, a lithium-philic oxide layer is introduced on the inner wall and surrounding of the micro-pit structure.

[0022] 4) The present invention adopts a simple operation process. First, an artificial interface layer of reduced graphene oxide is introduced by chemical coating to improve the serious side reactions on the interface and the uneven deposition of lithium ions on the microscopic scale. Then, a micro-pit array structure is introduced by means of multiple low-power laser etching to adjust the current density distribution on the surface of the current collector. The prepared composite 3D current collector combining the artificial interface layer and the micro-pit array structure effectively improves the compatibility problem between the two and brings out the advantages of both.

[0023] 5) The preparation process is simple, and a treatment method of first adding an artificial interface layer and then modifying the structure is adopted to prepare a composite 3D current collector with excellent performance, effectively reducing costs and improving production efficiency.

[0024] 6) The lithium copper half-cell assembled with the current collector prepared by the present invention has excellent cycle performance at 2 mA / cm -2 The current density can be stably cycled for more than 85 times.

[0025] 7) After a certain number of cycles, the current collector is taken out from the lithium-copper half-cell, and its top plane is observed through SEM. It can be found that compared with ordinary porous copper foil, the top surface of the prepared current collector always presents a stacked growth of lithium metal grains during the cycle process. The internal structure is compact and the lithium metal grains are tightly combined, which can effectively reduce its side reactions with the electrolyte.

[0026] The core difference between the present invention and the CN110212153A patent is that the purpose of adding graphene in the patent is to improve the interface performance between the current collector and the positive and negative electrode materials, such as bonding strength, interface resistance, etc. In the present invention, the purpose of adding a graphene interface layer on the surface of the current collector is to improve the interface performance between the negative electrode interface and the electrolyte. The prepared composite current collector is directly used as the negative electrode, and the positive / negative electrode material is not coated on the surface of the current collector. In addition, the method adopted by the CN110212153A patent is to first corrode the metal substrate to obtain a current collector with a convex and concave structure, and then coat the graphene interface layer. This method first adds a graphene interface layer on the surface of the planar current collector to avoid uneven thickness of the graphene interface layer caused by protrusions or depressions; then, a three-dimensional lattice is introduced on the surface of the current collector by laser etching. On the one hand, the graphene interface layer can effectively improve the interface side reaction between the current collector and the electrolyte, and on the other hand, the evenly distributed three-dimensional lattice can effectively induce a uniform distribution of current density on the surface of the current collector. This method can achieve uniform deposition of lithium metal on the negative electrode interface, effectively alleviating the appearance of lithium dendrites. During the battery cycle, the lithium metal grains on the surface of the current collector prepared by this method are tightly stacked and have a complete structure. Compared with the moss-like distribution and loose structure of the deposition morphology in the control group, the lithium metal deposition morphology is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Optical microscope image of the current collector prepared in Example 1;

[0028] Figure 2 Coulomb efficiency curve of the current collector prepared in Example 1 during the cycle;

[0029] Figure 3 Surface deposition morphology of the current collector prepared in Example 1 after a certain number of cycles; among them, (a) and (b) are porous copper foils; (c) and (d) are current collectors prepared by the present invention. DETAILED DESCRIPTION

[0030] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.

[0031] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention but are not intended to limit the present invention.

[0032] Example 1

[0033] The current collector preparation method of this embodiment is as follows:

[0034] 1) First, the purchased commercial copper foil (thickness of 20-50 μm) is cleaned with alcohol, acetone and other solutions to remove the oxide layer with uneven distribution and inconsistent thickness on the surface.

[0035] 2) Then immerse the treated copper foil in a graphene oxide suspension (concentration of 0.5-1.0 mg / ml, solvent is deionized water), ensure that the copper foil is completely immersed in the suspension, the immersion time is 12h-24h, and the temperature is room temperature. After the immersion time is over, put the copper foil with graphene oxide attached to the surface into a vacuum drying oven, set the temperature to 150-180°C, and the vacuum drying time is 8h-12h. After the above treatment, a layer of reduced graphene oxide artificial interface layer is evenly attached to the surface of the current collector. After bending, the graphene oxide interface layer is still tightly combined with the surface of the copper foil, and no shedding occurs.

[0036] 3) Place the current collector coated with graphene under the laser etching instrument, import the pattern to be etched into the software, and set the main parameters such as laser etching power and speed. In this patent, the laser pattern is a uniformly distributed micro-pit array dot matrix, the aperture is set to 50-75μm, and the hole spacing is set to 50-200μm; the laser etching scanning speed is set to 100-500Hz, the scanning power is set to 10W, and the number of scans is set to 5-10 times. After laser treatment, due to the small aperture and the low laser power set, the graphene coating layer outside the micropores is not damaged. The present invention obtains a three-dimensional current collector with a surface coated with graphene through simple chemical coating and laser treatment, and at the same time, a lithium-philic Cu is formed in situ on the inner wall of the micro-pit structure. x O oxide layer.

[0037] The artificial interface layer of reduced graphene oxide chemically coated on the surface of this embodiment is replaced with a hollow carbon nanosphere interface layer or a hexagonal boron nitride interface layer, and the coating treatment can be carried out according to the same process flow. The 3D composite current collector designed after process parameter optimization can meet different performance requirements.

Claims

1. A method for preparing a composite 3D negative electrode current collector for a lithium metal battery, characterized in that It is done as follows: 1) Clean the copper foil to remove the surface oxide layer; 2) soaking the cleaned copper foil in a graphene oxide suspension, and vacuum drying the copper foil with graphene oxide attached to the surface after soaking; 3) The copper foil with graphene oxide attached to the surface after drying is patterned by laser etching to obtain a three-dimensional current collector with graphene coated on the surface.

2. The method for preparing a composite 3D negative electrode current collector for a lithium metal battery according to claim 1, characterized in that The copper foil has a thickness of 20-50 μm.

3. The method for preparing a composite 3D negative electrode current collector for a lithium metal battery according to claim 1, characterized in that The concentration of the graphene oxide suspension is 0.5-1.0 mg / mL.

4. The method for preparing a composite 3D negative electrode current collector for a lithium metal battery according to claim 1, characterized in that The soaking time is 12h-24h, and the soaking temperature is room temperature.

5. The method for preparing a composite 3D negative electrode current collector for a lithium metal battery according to claim 1, characterized in that The vacuum drying temperature is 150-180° C., and the vacuum drying time is 8h-12h.

6. The method for preparing a composite 3D negative electrode current collector for a lithium metal battery according to claim 1, characterized in that The laser-etched pattern is a pattern composed of uniformly distributed micro-pit array lattices.

7. A method for preparing a composite 3D negative electrode current collector for a lithium metal battery according to claim 1 or 6, characterized in that The laser etching process conditions are as follows: the aperture is set to 50-75 μm, the hole spacing is set to 50-200 μm, the laser etching scanning speed is set to 100-500 Hz, the scanning power is set to 10 W, and the number of scans is set to 5-10 times.

8. The use of a composite 3D negative electrode current collector for a lithium metal battery prepared as claimed in claim 1, characterized in that The composite 3D negative electrode current collector for lithium metal batteries is used to prepare lithium copper half-cells.

Citation Information

Patent Citations

  • Multilayer body and preparation method thereof

    CN107579201A

  • Graphene application in battery

    CN108140844A

  • Current collector and preparation method thereof

    CN110212153A

  • Defective graphene and lithium metal battery

    CN111074233A

Cited By

  • Lithium metal battery current collector with composite structure and preparation method thereof

    CN120072954A